2020
DOI: 10.1136/jitc-2020-000911
|View full text |Cite
|
Sign up to set email alerts
|

Tim-3 finds its place in the cancer immunotherapy landscape

Abstract: The blockade of immune checkpoint receptors has made great strides in the treatment of major cancers, including melanoma, Hodgkin’s lymphoma, renal, and lung cancer. However, the success rate of immune checkpoint blockade is still low and some cancers, such as microsatellite‐stable colorectal cancer, remain refractory to these treatments. This has prompted investigation into additional checkpoint receptors. T-cell immunoglobulin and mucin domain 3 (Tim-3) is a checkpoint receptor expressed by a wide variety of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
250
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 303 publications
(261 citation statements)
references
References 102 publications
(90 reference statements)
8
250
0
3
Order By: Relevance
“…When complexed with Tim-3 on the cell surface, galectin-9 induces downstream signalling of differential intensity [8][9][10], depending on the type of human myeloid and lymphoid cells [11]. In myeloid cells, galectin-9 primarily triggers growth factor type responses, while in lymphoid cells it induces proapoptotic signalling [10][11][12][13]. Galectin-9, together with Tim-3, can be shed from the cell surface by proteolytic enzymes, thus being released into the tumour microenvironment or blood [2].…”
Section: Introductionmentioning
confidence: 99%
“…When complexed with Tim-3 on the cell surface, galectin-9 induces downstream signalling of differential intensity [8][9][10], depending on the type of human myeloid and lymphoid cells [11]. In myeloid cells, galectin-9 primarily triggers growth factor type responses, while in lymphoid cells it induces proapoptotic signalling [10][11][12][13]. Galectin-9, together with Tim-3, can be shed from the cell surface by proteolytic enzymes, thus being released into the tumour microenvironment or blood [2].…”
Section: Introductionmentioning
confidence: 99%
“…In silico analysis of 5’ upstream and the promoter region of HAVCR2 gene predicted localization of putative binding sites for the TFs: GATA-1, YY-1, p300, HNF-3b, Pbx-1, RARa, NFE2, MZF-1, and GATA-3 ( 57 ). The T-bet and NFIL3 (Nuclear Factor, Interleukin 3 Regulated) TFs have been reported as being involved in the regulation of HAVCR2 gene in T cells ( 224 ).…”
Section: T Cell Immunoglobulin and Mucin-domain Containing-3mentioning
confidence: 99%
“…The authors also suggested that the TME could be directly affected by TIM-3, which leads to decreased immune surveillance and tumour clearance [ 276 ]. Preclinical data pointed out the relevance of blocking TIM-3 together with PD-1, in particular, in several cancer models [ 277 ]. These data led to the clinical development of TIM-3 antibodies, which are being tested in combination with anti-PD-1/L1 mAbs.…”
Section: Immune Checkpoint Blockade In B-cell Lymphomamentioning
confidence: 99%